2022
DOI: 10.3390/biology11121789
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Baseline Obesity Prevalence and Its Association with Perceived Health and Physical Performance in Military Officers

Abstract: Increasing obesity rates among USA military members vary by age, pay grade, and measurement methods and threaten force fitness and readiness. Limited research has directly measured obesity among officers; those enrolled in graduate school at the Command and General Staff College (CGSC) face additional demands and increased obesity risk. This study compared obesity measurements and performance on the Army Physical Fitness test and self-rated health for a sample of mostly CGSC officers. Participants (n = 136, 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our findings are also consistent with earlier regression analytic findings for the British and the French Army reported by Sanderson et al and Quertier et al [ 15 17 , 23 ]. In contrast to their findings, age played a minor role in our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are also consistent with earlier regression analytic findings for the British and the French Army reported by Sanderson et al and Quertier et al [ 15 17 , 23 ]. In contrast to their findings, age played a minor role in our results.…”
Section: Discussionsupporting
confidence: 93%
“…Referring to the above mentioned prevalence of obesity, earlier studies reported a prevalence of 10% (2016–2017) in the French Armed forces, 12% (2014) in the UK Armed forces, and 15% (1999–2009) in the Czech Armed forces [ 15 , 17 , 18 , 23 ]. More current data for the U.S. Armed Forces published by Hollerbach et al in 2022 reported an obesity prevalence of 18.5% [ 23 ], similar to our findings of 18%, and which possibly reflects more accurately the current state of increasing obesity prevalence in society in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower rates of obesity (18 versus 37%) and hypertension (13% versus 30%) were seen among ADSM compared to the overall US population. 16 , 17 It is unclear the extent to which the prevalence and correlates of perceived health status would be similar across US military and general populations. Limited research among active duty Air Force recruits and Army personnel suggests that perceived health status was associated with harmful substance use, obesity, depression, poor sleep quality as well as outcomes such as increased risk of future hospitalization and illness-related ambulatory care visits.…”
Section: Introductionmentioning
confidence: 99%